Gallium-doped thermochemically treated titanium reduces osteoclastogenesis and improves osteodifferentiation - Piñera-Avellaneda, David; Buxadera-Palomero, Judit; Ginebra, Maria-Pau; Rupérez, Elisa; Manero, José María (Frontiers in Bioengineering and Biotechnology, 2023)
Excessive bone resorption is one of the main causes of bone homeostasis alterations, resulting in an imbalance in the natural remodeling cycle. This imbalance can cause diseases such as osteoporosis, or it can be exacerbated in bone cancer processes. In such cases, there is an increased risk of fractures requiring a prosthesis. In the present study, a titanium implant subjected to gallium (Ga)-doped thermochemical treatment was evaluated as a strategy to reduce bone resorption and improve osteodifferentiation. The suitability of the material to reduce bone resorption was proven by inducing macrophages (RAW 264.7) to differentiate to osteoclasts on Ga-containing surfaces. In addition, the behavior of human mesenchymal stem cells (hMSCs) was studied in terms of cell adhesion, morphology, proliferation, and differentiation. The results proved that the Ga-containing calcium titanate layer is capable of inhibiting osteoclastogenesis, hypothetically by inducing ferroptosis. Furthermore, Ga-containing surfaces promote the differentiation of hMSCs into osteoblasts. Therefore, Ga-containing calcium titanate may be a promising strategy for patients with fractures resulting from an excessive bone resorption disease.